Student Well-Being in the Perception of Madrasah Ibtidaiyah Students - Nur Wahyuni, Esa; Yuli Efiyanti, Alfiana; Aziz, Rahmat; Mangestuti, Retno; Maksum, Ali (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to investigate students' perception of student well-being based on five aspects, namely having, loving, being, spirituality, and healthy. This study uses a mixed-method approach with a total of 541 madrasah ibtidaiyah students in grades 5 and 6 as research subjects. Quantitative data collection uses a Student Perception Questionnaire of student well-being, while for qualitative data obtained through interviews. The results showed that first, the majority of student well-being was in the high category. Likewise, in every aspect of student well-being, which includes having, loving, being, and healthy, it also shows a high level of well-being. However, in the element of spirituality, most students show a low level of wellbeing. Second, compared to the other four aspects, the loving aspect has a higher frequency. This result shows that the aspect of social relations (loving) in school as the most critical aspect of improving student well-being. Third, from a gender perspective, the results of the study show that the well-being of female subjects is higher than male subjects, although not significantly.